A comparative study of commonly used batteries in household rooftop solar battery systems based on test data of commercial batteries. (August 2022) - Saha, S.; Hassan, M.U.; Liebrich, F.; Mendis, N.; Islam, S.N.; Mahmud, M.A.; Haque, M.E.
Highlights: Performance evaluation of rooftop solar battery systems. Performance evaluation using test data from commercial solar batteries. Both the technical and economic performances have been analysed. Abstract: In recent years, uptake of grid integrated household rooftop solar battery systems (RSBSs) has increased significantly. This paper presents a thorough analysis on technical and economic performances of the common types of batteries featuring in RSBSs using test data of different commercial batteries. In this study, number of complete cycles, battery voltage deviation during a discharge period, discharge capacity, energy output and round trip efficiency are considered as the technical performance indicators of a RSBS battery. While evaluating the economic performance, the expected household net incomes from the RSBSs of different battery types have been calculated considering the uncertainties in household electricity demand and solar power generation using Monte-Carlo Simulation. Moreover, the payback period of RSBSs of different battery types have been predicted in this study. The outcomes of this study provide a clear insight to the performance of commonly used batteries in the RSBS, which will aid the end users in making educated decisions while choosing RSBSs.